Laser Radiation as an Adjunct to Nonsurgical Treatment of Periodontal Disease - Núñez, Juan Antonio García; Sánchez, Alicia Herrero; Kass, Ana Isabel García; Hernández, Clara Gómez (IntechOpen, 2012)
None